'The apocalyptic battle' - Nicola Karcher; Kjetil Braut Simonsen (Nordisk Judaistik, 2024)
Conspiracist antisemitism was an integral part of national-socialist propaganda in Norway between 1940 and 1945. An imaginary entity called ‘International Jewry’ was represented as the sinister force behind phenomena such as Communism, liberalism, capitalism and cultural decadence. This article analyses the argumentation and functions of conspiracist antisemitism as it was disseminated by three journals in Nazi-occupied Norway: the Norwegian edition of the German antisemitic journal Welt-Dienst (Verdens-Tjenesten), the weekly Hirdmannen and the antisemitic periodical Nationalt Tidsskrift. While these publications represented history and politics as an apocalyptic battle between the so-called Nordic-Germanic peoples and an alleged ‘Jewish conspiracy’, their argumentation differed in several aspects. Whereas Verdens-tjenesten was first and foremost an anti-Jewish news agency, Nationalt Tidsskrift and Hirdmannen were more focused on attacking the Norwegian Jews directly. However, according to all three journals, the national-socialist revolution was an act of redemption, from Jews as well as from ‘Jewish ideas’.